Penerapan Standar Akuntansi Nasional Pada Organisasi Nirlaba Bidang Sosial Kemanusiaan di Bali - Made Aristia Prayudi; Made Narsa (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The purpose of this study are to evaluate organization compliance level with Indonesian GAAP No. 45: ‘Financial Statement of Not-for-Profit Organization’, investigate preparers’ and users’ perceptions toward the standard; and determine whether or not there is a significant difference between the perceptions of the two groups. Data were collected through questionnaires were distributed to 30 financial staffs of 10 units of Indonesian Red Cross Society (as the preparer group) and to 30 local government officers (as the user group) of Health Department, Social Service Department, and Public Welfare Bureau in Bali Province of Indonesia. The data was analyzed descriptively and using the Independent t-Test and Mann-Whitney test. The results show that only one-third of the organizations are categorized as compliant, users have higher perceptions of the importance and usefulness of the standard and there are significant differences between the groups in their perception toward the standard.